Social Media Marketing Relations, Brand Awareness to Brand Loyalty Through The Brand Image - Heskiano Heskiano; Tantri Yanuar Rahmat Syah; Mohamad Reza Hilmy (Journal of Multidisciplinary Academic, 2020)
The increasing number of hospitals built by both private and government parties requires a hospital to be ready to compete both in competing with domestic hospitals and in competing with international hospitals. This study aims to analyze the effect of social media marketing activities, brand awareness of RSIA X on the brand loyalty of outpatients in the midwifery section with brand image as an intervening variable. This study uses a quantitative approach, survey methods and correlation techniques with a non-experimental design using a cross-sectional study approach with a sample of 160 patients who are outpatient in the obstetrics department of RSIA X and become a follower in social media accounts of RSIA X. Social media marketing activities, brand awareness are independent variables. Brand image is an intervening variable and brand loyalty is a dependent variable. This study uses a questionnaire using a Likert scale while testing data analysis using SEM. The results showed a social media marketing and brand awareness had a positive and significant effect on brand loyalty mediated by brand image.